The Role of Educational Institutions in Countering Political Polarization: Building Inclusive Communities and Civic Engagement - Muhtar Muhtar; Budi Setiyono; Fitriyah Fitriyah; Nur Hidayat Sardini (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Political polarization has become increasingly prevalent worldwide, posing significant challenges to social cohesion, democratic governance, and civic participation. Various factors, including ideological divisions, socio-economic disparities, and the rise of digital echo chambers, have exacerbated this phenomenon. Amidst this backdrop, educational institutions have emerged as pivotal actors in addressing political polarization by fostering inclusive communities and promoting civic engagement among students and faculty members. This study aims to identify the key challenges and opportunities faced by educational institutions in addressing political polarization, examine the effectiveness of existing interventions and programs, and propose evidence-based recommendations for enhancing the role of educational institutions in building inclusive communities. This study employs a qualitative research design utilizing a literature review as the primary methodological approach. The data for this research are obtained from various scholarly sources, including academic journals, books, reports, and policy documents, accessed through academic databases, institutional repositories, and online libraries. In conclusion, this research sheds light on the crucial role that educational institutions play in combating political polarization by fostering inclusive communities and promoting civic engagement among students. Through an analysis of the various mechanisms and strategies employed, it becomes evident that educational institutions are vital platforms for bridging ideological divides and nurturing a culture of tolerance and respect for diverse perspectives.